Determining the consumer decision making styles of young-adult Malays from universities in Kedah, Pulau Pinang, and Perlis / Maznah Wan Omar…[et al.] - Wan Omar, Maznah; Mohd Ali, Mohd Noor (Research Management Institude, 2004)
The research explores the interrelations between individuals’ learning styles and their consumer decision-making styles. A Secondary Learning Styles Inventory was develop based on the study done by Sproles, E.K. and Sproles, G.B., to measure six characteristics of learning and a Consumer Styles Inventory (CSI) were used to measure eight characteristics of consumer decision making. Consumers decision-making styles were measured by 51 five-point Likert-scale items with strongly disagree and strongly agree as the end point. A Principal axis factoring (PAF) was used. The anti-image correlation matrix was used to assess the sampling adequacy of each variable. Variables with a measure of sampling accuracy that falls below the acceptable level of .5 were excluded from the analysis. Bartlett’s test of sphericity and the Kaiser-Meyer-Olkin measure of sampling adequacy were also used to determine the factorability of the matrix as a whole. Principal axis factoring with varimax rotation was used to confirm the study. The research reported in this paper explores the relationships between individuals’ learning styles and their consumer decision-making styles. The traits use to confirm this study was based on the study done by Sproles (1985), where Sproles named and described these traits as: (1) “Perfectionism” - consumers seek the very best quality products, have high standards and expectations for consumer goods, and are concerned with the function and quality of products; (2) “Value Conscious, Value for Money Orientation ' - consumers are low-price conscious, look for the best value for the money, and are likely to be comparison shoppers. (3) ’Brand Consciousness' - consumers are oriented toward expensive and well-known national brands and feci price is an indicator of quality; (4) Novelty-Fad-Fashion Consciousness -consumers gain excitement and pleasuie ftom seeking out new tilings" and ate conscious of the new fashions and fads and (5) "Shopping Avoider-Time Saver-Satisfier” - consumers avoid shopping, "make shopping trips tapidly,” and may forego some quality for time and convenience (1985 81)., (6) "Confused, Support-Seeking Decision-maker" - consumers find the marketplace confusing, view brands as alike, and seek help from friends (1985). This research also used a Consumer Styles Inventory (CSI), which was introduced by Sproles and Kendall. Consumer Styles Inventory (CSI) used by Sproles and Kendall were an instrument use to measure “characteristics of decision making”. Cronbach's alpha was used to established scale reliabilities. Since this research is based on the model proposed by Sproles and Kendell, where items that loaded above .4 as reliable, our research also uses the same scale i.e .4 and above is classified as having satisfactory reliabilities. Only two Style Characteristics tested on Young-Malay adult shows an unsatisfactory reliability. They are “Recreational-Shopping Conscious (Factor 3) which is considered as non reliability. The reading is .2776 and the second Style Characteristics that is below the reliability level is “Habitual, Brand -Loyal" (Factor 7) with readings equal to .3831.